Alternative pathways to complexity: a collection of essays on architecture, economics, power, and cross-cultural analysis in honor of Richard E. Blanton - Fargher, Lane F., editor; Heredia Espinoza, Verenice Y., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Focuses on architecture, economics, and power in the evolution of complex societies. Case studies from Mesoamerica, Asia, Africa, and Europe examine the relationship between political structures and economic configurations of ancient chiefdoms and states through a framework of comparative archaeology.--Provided by publisher.
It was the economy, stupid / Stephen A. Kowalewski -- Alternative pathways to power in formative Oaxaca / Arthur A. Joyce and Sarah B. Barber -- Built space as political fields: community vs. lineage strategies in the Tequila Valleys / Christopher S. Beekman -- Complexity without centralization: corporate power in postclassic Jalisco / Verenice Y. Heredia Espinoza -- Central Precinct Plaza: replication and corporate groups in Mesoamerica / Barbara L. Stark -- Featherwork as a commodity complex in the late postclassic Mesoamerican world system / Frances F. Berdan -- Classic Maya marketplaces and exchanges: examining market competition as a factor for understanding commodity distributions / Lisa J. LeCount -- Enduring nations and emergent states: rulership, subjecthood, and power in early Scandinavia / T.L. Thurston -- The Bakitara (Banyoro) of Uganda and collective action theory / Peter Robertshaw -- Cognitive codes and collective action at Mari and the Indus / Rita Wright -- "We shape our buildings and afterwards our buildings shape us": interpreting architectural evolution in a Sinhalese Village / Deborah Winslow -- Network strategy and war / Peter N. Peregrine and Carol R. Ember -- Framing the rise and variability of past complex societies / Gary M. Feinman and Linda M. Nicholas -- Pathways to power: corporate and network strategies; staple and wealth finance; and primary and secondary states / Tim Earle -- Corporate power strategies, collective action, and control of principals: a cross cultural perspective / Lane F. Fargher.
Keywords: Blanton, Richard E.; Technological complexity; Archaeology -- Cross-cultural studies; Architecture and archaeology; Economic anthropology; Social archaeology